STUDY OF THE PHYTOCHEMICAL COMPONENTS OF ANABASIS APHYLLA L. GROWING IN UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
This article examines the botanical description, chemical composition, and potential uses of Anabasis aphylla L. in traditional medicine. Anabasis aphylla L. is a plant from the Amaranthaceae family, adapted to life in arid and saline regions, and distinguished by its high toxicity. Alkaloids, flavonoids, coumarins, tannins, saponins, glycosides, and other bioactive compounds have been identified in the plant. The article also analyzes the distribution of phytocomponents in the extracts from the aerial and root parts of the plant. Some parts of the plant are used in folk medicine, but caution is required due to its toxicity. Alkaloids and flavonoids found in the plant show therapeutic properties, including antimicrobial, antiviral, anti-inflammatory, and anticancer effects. The article provides a detailed analysis of the bioactive substances of Anabasis aphylla L. and their medicinal properties.